Formation of fibroblastic reticular network in the brain after infection with neurovirulent murine coronavirus. Issue 6 (28th April 2016) - Watanabe, Rihito; Kakizaki, Masatoshi; Ikehara, Yuzuru; Togayachi, Akira
Abstract : cl‐2 virus is an extremely neurovirulent murine coronavirus. However, during the initial phase of infection between 12 and 24 h post‐inoculation (hpi), the viral antigens are detected only in the meninges, followed by viral spread into the ventricular wall before invasion into the brain parenchyma, indicating that the viruses employ a passage between the meninges and ventricular wall as an entry route into the brain parenchyma. At 48 hpi, the passage was found to be constructed by ER‐TR7 antigen (ERag)‐positive fibers (ERfibs) associated with laminin and collagen III between the fourth ventricle and meninges at the cerebellopontine angle. The construct of the fibers mimics the reticular fibers of the fibroblastic reticular network, which comprises a conduit system in the lymphoid organs. In the meninges, ERfibs together with collagen fibers, lining in a striped pattern, made up a pile of thin sheets. In the brain parenchyma, mature ERfibs associated with laminin were found around blood vessels. Besides mature ERfibs, immature Erfibs without associations with other extracellular matrix components like laminin and collagen appeared after infection, suggesting that the CNS creates a unique conduit system for immune communication triggered by viral invasion.